2021
DOI: 10.1039/d0bm01576h
|View full text |Cite
|
Sign up to set email alerts
|

Ag2S quantum dot theragnostics

Abstract: The silver sulfide quantum dot (Ag2S QD) as a theragnostic agent has received much attention because it provides excellent optical and chemical properties to facilitate diagnosis and therapy simultaneously. Ag2S...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…At present, silver sulfide quantum dots (Ag 2 S QDs) enjoy almost non-existent toxicity and attractive fluorescence properties, which can cover the area between infrared and NIR, making them ideal objects for metal ion detection . As a kind of near-infrared fluorescent agent, a silver sulfide quantum dot has exerted tremendous fascination on biomedical labeling and imaging in recent years. Although great progress has been made in the synthesis and application of nano-silver sulfide quantum dots in the past decade, there are still challenges in the biological system. The physical and chemical pathways of traditional Ag 2 S quantum dot synthesis usually require harsh conditions and toxic reagents, including modified particle size engineering surface ligands.…”
Section: Introductionmentioning
confidence: 99%
“…At present, silver sulfide quantum dots (Ag 2 S QDs) enjoy almost non-existent toxicity and attractive fluorescence properties, which can cover the area between infrared and NIR, making them ideal objects for metal ion detection . As a kind of near-infrared fluorescent agent, a silver sulfide quantum dot has exerted tremendous fascination on biomedical labeling and imaging in recent years. Although great progress has been made in the synthesis and application of nano-silver sulfide quantum dots in the past decade, there are still challenges in the biological system. The physical and chemical pathways of traditional Ag 2 S quantum dot synthesis usually require harsh conditions and toxic reagents, including modified particle size engineering surface ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–sulfide based semiconductors MS x (except ZnS) as their narrow band gap can facilitate the light absorbance at a wide wavenumber of visible to infrared range. , Among the metal sulfides, Ag 2 S has attracted great attention in the field of photocatalysis, as its narrow band gap (∼1 eV) and relatively larger absorption coefficients (∼10 6 cm –1 ), high chemical stability, and negligible toxicity. More recently, Masoud et al reported a porous hollow Ag/Ag 2 S/Ag 3 PO 4 catalyst: it has a suitable band gap energy of 2.17 eV and showed high efficiency in the photocatalytic degradation of tetracycline under simulated sunlight irradiation. They attributed the good photocatalytic activity of Ag/Ag 2 S/Ag 3 PO 4 nanocomposites to the unique hierarchical architectures, which promoted visible-light harvesting, reduced a recombination, and boosted the separation of electron–hole pairs that originated from the as-formed heterojunctions .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal sulfides have received extensive attention in biomedical applications due to their fascinating properties, such as low-cost, suitable bandgap, environmentally high stability, etc. [24,26,203,[259][260][261][262][263][264] SnS is also biocompatible and nontoxic due to its poor absorption by human body and rapid excretion in faeces. [203,265] Up to now, 0D SnS QDs, 2D SnS NSs, and triangular SnS nanopyramids were used in biomedical applications such as photothermal therapy, chemo-therapy agents, and photoacoustic imaging.…”
Section: Biomedical Applicationsmentioning
confidence: 99%